The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1099/jmm.0.05234-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Ehrlichia chaffeensis infection in beagles

Abstract: A canine model for human monocytic ehrlichiosis was used to assess persistent infection and antigenic variation of Ehrlichia chaffeensis. Two beagle dogs were infected subcutaneously with E. chaffeensis Arkansas strain. The dogs were observed for 6 months after inoculation for clinical signs, blood chemistry changes, antibodies to E. chaffeensis and presence of E. chaffeensis in the blood. Both dogs developed thrombocytopenia, but exhibited normal body temperatures during the entire course of infection. In one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
29
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 23 publications
7
29
0
1
Order By: Relevance
“…The sera from two male beagle dogs (dog ACC and dog ADJ) experimentally infected with E. chaffeensis at 6 months of age were used in this study, and infection of the dogs was reported elsewhere previously (38). Briefly, the dogs were infected by subcutaneous inoculation of 10 6 E. chaffeensis (Arkansas strain)-infected DH82 cells (7).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sera from two male beagle dogs (dog ACC and dog ADJ) experimentally infected with E. chaffeensis at 6 months of age were used in this study, and infection of the dogs was reported elsewhere previously (38). Briefly, the dogs were infected by subcutaneous inoculation of 10 6 E. chaffeensis (Arkansas strain)-infected DH82 cells (7).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant P28 fusion proteins were purified with ProBond resin (Invitrogen), a nickel-charged Sepharose resin that binds to the His tag. The genes p28-15 and p28-19 were cloned into the PCR T7/CT TOPO vector as previously described (38). The genes for GP120 and P110, outer membrane proteins of E. chaffeensis, were cloned previously in the pGEX expression vector and expressed as GST fusion proteins in E. coli (32,33).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, experimental study has documented the dog's susceptibility to E. chaffeensis infection and its role as a natural host for E. chaffeensis. 10 Because of the possibility that dogs under natural conditions can be infected by both E. canis and E. chaffeensis, there is need for laboratory tests to differentiate between the 2 bacteria. Sequencing of the genes encoding the p30 surface protein and 16S ribosomal RNA (16S rRNA) has revealed a close genotypical relation between E. canis and E. chaffeensis.…”
mentioning
confidence: 99%